Diseño de estrategias promocionales de la ruta turística del cerro sagrado wingopana de la parroquia Canchagua del cantón Saquisilí provincia de Cotopaxi. - Oña Oña, Hilda Mercedes (2018)
The project was carried out in the Canchagua parish of the Saquisilí canton of the Cotopaxi province. This project aimed to design promotional strategies for the Cerro Sagrado Wingopana tourist route through advertising tools for the promotion of the route that allows achieving the use of the resources it possesses. A diagnosis of the current situation was made in the aspects; socio-cultural, economic, environmental and tourist of the Canchagua parish, in which the tourist route with natural and cultural attractions for the development of tourism is located. A rapid market survey was carried out on people who were visiting the province of Cotopaxi through the application of surveys to tourists, the interpretation of results was carried out where important information was obtained and the supply and demand for the route could be defined. tour. The offer of the Cerro Sagrado Wingopana tourist route was determined, as well as the tourist plant, infrastructure and complementary services. The demand was identified through the data obtained in the survey carried out. Subsequently, the information obtained was analyzed and promotional strategies were designed in order to increase the influx of tourists on the route, where they can carry out sustainable tourism activities that contribute to the revitalization of the local economy. Promotional strategies of brand or image of the route were designed, the same one that is formed from; a logo, isotype, and slogan, attraction strategies were also designed such as; web page, eMail marketing or mailing, blog, a Facebook page, and a twitter page, promotion strategies were also developed in tourism fairs, and merchandising strategies with personalized objects with the logo of the route, all these strategies will help to promote the tourist route of the Wingopana hill of the Canchagua parish and obtain an increase in tourists